Study of conditioning of national team mogul skiers - Analysis of conditioning for Winter Olympic Games - - Suzuki, T.; Kono, I.; Akimoto, T. (International Journal of Sport & Health Science, 2006)
The purpose of this study was to evaluate the conditioning of elite mogul skiers through the 2001-2002 Federation International de Ski season (that is, the World Cup freestyle competition and the Salt Lake City Winter Olympic Games) using a single-case study method. Four elite mogul skiers were observed independently and measured in parameters such as athletic condition. The results indicated that during the competition season there was no significant change in the conditioning of the world-class skiers of this group. However, the conditioning of the intermediate skiers did change. It was concluded that it is preferable to use the single-case study method when analyzing physical conditioning.